Analisis Literatur tentang Strategi Manajemen Laboratorium IPA dalam Meningkatkan Kualitas Praktikum di SMA - Ardela Noviati Muhlis; Kharisma Putri Kholifah; Zahwa Zakiatun Nuha (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the strategy of natural science laboratory management in improving the quality of practicums in senior high schools. This study uses a literature review approach by examining various academic sources related to laboratory management. The results of the analysis indicate that effective laboratory management includes five main strategies, namely management of equipment, materials, data, laboratory personnel training, and cost budgeting. The success of implementing this strategy depends on the implementation of supporting factors such as work safety, infrastructure quality, personnel capabilities and excellent data management systems. However, there are still many obstacles, including limited facilities and infrastructure, lack of professionals, inadequate budgets, and optimal planning and implementation of practices. Comprehensive improvements in laboratory management are expected to enable learning science to be implemented in a more optimal and sustainable manner.